Nutrition Education on Obesity Prevention for Students at Insan Cendekia Syech Yusuf High School - Damayati, Dwi Santy; Ibrahim, Irviani A.; Syam, Aditya Mulyadi; Munifah, Andi Naila; Aisyah, Andi Qaila Nur; Asrafiah N; Anugrah, Aulia (Universitas Islam Negeri Alauddin Makassar, 2026)
The WHO reports that the global prevalence of adolescent obesity has exceeded 20%. This condition emphasizes the importance of promotional interventions through nutrition education in Islamic schools that are prone to unbalanced diets and limited physical activity. This community service activity was carried out at Insan Cendekia Syekh Yusuf High School on September 19, 2025, involving 49 students in grades XI and XII. The activity methods included a pre-test, interactive nutrition education, provision of healthy food, and a post-test. The results of the paired t-test showed a significant effect of nutrition education on increasing student knowledge, with the average score increasing from 17.47 to 24.82 (p < 0.001). These findings reinforce the importance of nutrition education in Islamic schools as a preventive strategy. Thus, this community service activity proved to be effective in improving adolescents' understanding of obesity and is recommended to be implemented continuously with the support of schools to shape healthy living behaviors.